Understanding the forces and critical features of a new reporting and budgeting system adoption by Indonesian local government. Issue 1 (8th February 2020) - Harun, Harun; Carter, David; Mollik, Abu Taher; An, Yi
Abstract : Purpose: This paper aims to critically explore the forces and critical features relating to the adoption of a new reporting and budgeting system (RBS) in Indonesian local governments. Design/methodology/approach: The study is based on an intensive analysis of document sources and interview scripts around the institutionalization of RBS by the Indonesian government and uses the adaption of Dillard et al. (2004) institutional model in informing its findings. Findings: The authors find that at the national level, the key drivers in RBS adoption were a combination of exogenous economic and coercive pressures and the wish to mimic accounting reforms in developed nations. At the local government level, the internalization of RBS is a response to a legal obligation imposed by the central government. Despite the RBS adoption has strengthened the transparency of local authorities reports – it limits the roles of other members of citizens in determining how local government budgets are allocated. Research limitations/implications: The results of the study should be understood in the historical and institutional contexts of organizations observed. Practical implications: The authors reinforce the notion that accounting as a business language dominates narratives and conversations surrounding the nature of government reporting and budgeting systems and how resource allocation is formulated and practiced. This should remind policymakers in other developing nations that any implementation of a new accounting technology should consider institutional capacities of public sector organizations and how the new technology benefits the public. Social implications: The authors argue that the dominant role of international financial authorities in the policymaking and implementation of RBS challenges the aim of autonomy policies, which grant greater roles for local authorities and citizens in determining the nature of the budgets and operation of local authorities. Originality/value: This study extends institutional theory by adapting the Dillard et al. (2004) model in explaining the forces, actors and critical features of a new accounting system adoption by local governments.